Enhancing the Number Recognition Ability of Group A Children through Number Ball Educational Play Tools (APE) at TK ABA Tanggul - Susilowati, Endang; Prayogo, Basuki Hadi; Suwargono, Trio (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to improve the cognitive ability of 4–5-year-old children in recognizing numerical symbols through the use of number ball educational play tools (APE) at Aisyiyah Bustanul Athfal Kindergarten for the 2024/2025 academic year. The background of this research lies in the low cognitive achievement at the early preoperational stage, where children require meaningful and concrete stimulation appropriate to their developmental level. This study is a Classroom Action Research (CAR) conducted in two cycles using the Kemmis & McTaggart model. The subjects were 15 Group A children. Instruments used included observation sheets and documentation. Pre-cycle results showed that only 26.7% of the children were in the